Insalubridade do profissional arquivista: um estudo de caso no Arquivo Guilherme de La Penha do Museu Paraense Emílio Goeldi/MPEG - MELO, Fernando Alex Sarmento de (2021)
This study aimed at the elaboration of a risk map, in the Guilherme de La Penha Archive at the Museu Emílio Goeldi (MPEG), located in Belém, capital of the state of Pará, Brazil, a Federal Public Institution for scientific research on the Amazon Which has several areas with the presence of insalubrity in the performance of its activities. The research aims to carry out the mapping of risks in the Guilherme de La Penha Archive in order to identify the existing risks, indicate the degree of these possible risks and indicate preventive measures for them. The method adopted was qualitative. The research is classified for purposes as descriptive and explanatory and as to the means as bibliographical. Data collection was performed "locally" through the application of two research tools, a check list and a multiple choice questionnaire with the file servers. With the development of the present study it was possible to identify the importance of the existence of the risk map in minimizing the risks of accidents that the professionals of the Institution archive are exposed daily, proposing improvements, through a folder of guidance of health security and a map of risks, these being the results of this research.